Introduction to the complex intervention concept and the research perspectives. (20th October 2021) - Skivington, K; Craig, P; Moore, L; Matthews, L; Simpson, S
Abstract:  : Few interventions are truly simple; complexity can arise from various sources, e.g.: Aspects of the intervention itself, such as the number of intervention components, the number of groups targeted, how dynamic the intervention is permitted to be. The context in which the intervention is developed and delivered, such as the social, political, economic, and geographical context. Complex intervention research should be approached with an awareness of these sources of complexity. Systems thinking can be helpful to understanding the dynamic interaction between interventions and their context. This presentation will introduce concepts of complex adaptive systems, e.g. feedback loops, adaptation, emergence, that should be considered when developing and evaluating complex interventions. It will then introduce participants to the research perspectives set out in the new framework: efficacy, effectiveness, theory-based, and systems perspectives. Each perspective is associated with a different type of research question, and therefore appropriate in different circumstances. The presentation will provide information to support participants to consider the research perspective(s) most suited to the research challenge that they are aiming to address. Main messages: There are multiple sources of complexity, each of which can affect how the intervention works or contributes to change. Complex intervention research can take an efficacy, effectiveness, theory-based, or systems perspective, the choice of which is based on what is known already and what further evidence would be most useful.